Investigating Metonymic Expressions in Communication - Shabir, M. (ENGLISH JOURNAL, 2016)
This paper was written as a result of an investigation concerning one of phenomena in language use, which is specifically related to metonymic expressions used by lecturers at one of universities in Bogor. The writer investigated deeply the patterns of metonymic expressions in communication and then analyzed which of those patterns of metonymy categorized as the most frequently used by the lecturers. The data presented in this paper was taken from communication activities by lecturers. Based on the data found during the investigation, it can be concluded that the lecturers seem to frequently use the pattern “institution for people responsible”. One clear reason for using this pattern is to economize the use of language.